RADIOLOGICAL FINDINGS IN X-LINKED HYPOPHOSPHATEMIA - (:unkn) unknown (ISTANBUL UNIV, FAC MEDICINE, PUBL OFF, 2020)
Radiological findings in X-linked hypophosphatemia are similar to, albeit less severe than, nutritional rickets. Loss of distinctness of the zone of provisional calcification, widening of the growth plate first in the long axis, followed by widening in the short axis, cupping of the metaphysis and irregularity (fraying) at the metaphyseal border are seen on X-rays of long bones. The severity of the findings can be assessed from bilateral anteroposterior X-rays of the wrists and knees using the Rickets Severity Score (RSS). RSS can be used at the time of diagnosis as well as for assessing response to treatment. The Radiographic Global Impression of Change Scale (RGI-C) is another scoring method which can be used during follow-up of patients.
Keywords: X-ray; rickets; scoring